Single crystal growth and characterization of superconducting LiFeAs - Morozov, Igor; Boltalin, Alexander; Volkova, Olga; Vasiliev, Alexander; Kataeva, Olga; Stockert, Ulrike; Abdel-Hafiez, Mahmoud; Bombor, Dirk; Bachmann, Anne; Harnagea, Luminita; Fuchs, Madeleine; Grafe, Hans-Joachim; et al. (Crystal growth & design, 2010)
Large and high quality single crystals of the new unconventional superconductor LiFeAs were grown by a new approach using the self-flux technique. Both energy dispersive X-ray spectroscopy and inductively coupled plasma mass spectroscopy revealed a stoichiometric Li/Fe/As composition. Measurements of the magnetic susceptibility reveal the superconducting transition at TC = 17 K with a very sharp ΔTC and a 100% shielding fraction and, thus, bulk superconductivity. This sharp transition is also found by measurements of the specific heat and by measurements of the temperature dependence of the resistivity. Nuclear quadrupole resonance (NQR) spectroscopy reveals a very sharp resonance line, with a much smaller line width than reported for all other FeAs superconductors, confirming the high ordering of the LiFeAs single crystals also on a local scale.